2012
DOI: 10.1016/j.ajhg.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequence Identifies RIPK4 as the Bartsocas- Papas Syndrome Locus

Abstract: Pterygium syndromes are complex congenital disorders that encompass several distinct clinical conditions characterized by multiple skin webs affecting the flexural surfaces often accompanied by craniofacial anomalies. In severe forms, such as in the autosomal-recessive Bartsocas-Papas syndrome, early lethality is common, complicating the identification of causative mutations. Using exome sequencing in a consanguineous family, we identified the homozygous mutation c.1127C>A in exon 7 of RIPK4 that resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
89
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 49 publications
2
89
0
3
Order By: Relevance
“…This likely explains the intraoral and esophageal fusions and the partial attachment of the limbs to the body wall in RIPK4 − / − mice (Figures 3b, d and f). Similar to the hypoplastic external genitalia observed in humans affected by PPS, 8,9 the genital tubercle was lacking in RIPK4 − / − mice (Figures 3f and 4a). …”
Section: G H and I)supporting
confidence: 68%
See 4 more Smart Citations
“…This likely explains the intraoral and esophageal fusions and the partial attachment of the limbs to the body wall in RIPK4 − / − mice (Figures 3b, d and f). Similar to the hypoplastic external genitalia observed in humans affected by PPS, 8,9 the genital tubercle was lacking in RIPK4 − / − mice (Figures 3f and 4a). …”
Section: G H and I)supporting
confidence: 68%
“…10,11 In addition, IRF6 (interferon regulatory factor 6) and RIPK4 have been implicated in PPS. 8,9,12 We found that similar to IRF6 mutants, 10,11,13 RIPK4 − / − mice 1 have a defective skin barrier function and cleft palate, and RIPK4 − / − keratinocytes fail to differentiate in vitro. In Xenopus, we show that IRF6 controls RIPK4 expression and that RIPK4 can rescue developmental defects imposed by IRF6 dysfunction, thereby identifying a novel genetic interaction between IRF6 and RIPK4.…”
mentioning
confidence: 77%
See 3 more Smart Citations